Policy brief: Launching the mission for 100 climate neutral cities in Europe : characteristics, critiques and challenges - Mccormick, Kes ; 0000-0002-5093-160X; Diamant, Lilly (Lund University, 2026)
This study critically explores the launch of the mission for 100 climate neutral cities in Europe. Key elements of the mission are introduced and analysed along with some of its challenges and ambiguities.
Developed as part of the Massive Urban Missions (MUM) project.
Keywords: Cities; Climate; Change